Sporting the glass jaw : views on women in sports - Maskalan, Ana (Array, 2020)
Sport is still understood as a traditional bastion of masculinity that exalts physical qualities such as strength and speed, and psychological traits such as aggression and perseverance, deeming women’s participation undesirable and unnecessary. Nevertheless, women for decades, in strict separation from men or within so-called “women’s sports”, were achieving results worthy of the attention of even the fiercest sceptics. Because of its nature founded in physicality, sport is still relatively seldom the area of political struggle for gender equality, although female athletes have occasionally done more for positive outcomes of that struggle than is acknowledged. In this paper, I discuss the ambivalent nature of sport contributing, on the one hand, to the essentialisation of genders in their differences and the petrification of power relations between them, and containing, on the other, indications of destruction or at least of corruption of the traditional, hierarchically established gender norms. The paper consists of four parts. In the first introductory part, I explain the reasons for concentrating my discussion on formalised competitive sports and approaches I am using. While emphasising the biopolitical aspects of the subject, I start my analysis with the description of a proclaimed guiding principles of contemporary sports contained in the spirit of Olympism. In the second part, I discuss the ontology of sport contained in the ideas of the founder of the modern Olympic Games Baron Pierre de Coubertin and the consequential factors influencing women ‘s participation in sports. These range from the perception of women’s allegedly debilitating physical and psychological traits, through hypersexualisation of female athletes’ body, or the attitude that it is not feminine enough, to the accusations that female athletes harm their health jeopardising, for example, the basic feminine duty – that of motherhood.